Design, Synthesis, and Biological Evaluation of N-Acylhydrazones and Their Activity Against Leishmania amazonensis Promastigotes - Caio Eduardo Oliveira Monteiro; João Carlos Martins Mafra; Nubia Boechat; Edson Roberto da Silva (Microorganisms, 2025)
Leishmaniasis is a significant public health concern, affecting millions and causing substantial mortality, thus urgently requiring more effective and safer treatments. This study explored the potential of 33 novel N-acylhydrazone-derived compounds against Leishmania amazonensis parasites, focusing on their inhibition of the Leishmania arginase enzyme and promastigote growth. Compounds 8 and 18 showed over 90% inhibitory activity against promastigote cultures after 72 h of treatment. Compound 8 showed an IC50 of 10.5 µM (9.4–11.8 µM), while compound 18 exhibited an IC50 of 42.8 µM (41.3–44.4 µM). The antipromastigote effects of these compounds highlight their potential for further new drug design. These findings offer a promising starting point for addressing the pressing need for new therapeutic options against leishmaniasis. In addition, we used web-based tools to predict the compounds’ toxicity and pharmacokinetic parameters. Despite the lack of inhibition against the L. amazonensis arginase enzyme, further investigation into the mechanisms of action of these compounds and in vivo efficacy could contribute to the development of safer and more effective treatments for this neglected tropical disease.